Design of High Gain Microstrip Patch Reader Array Antenna with Parasitic Elements for UHF RFID Application - Norzeli, Syamimi Mohd; Ismail, Ismarani; Md Din, Norashidah; Ali, Mohd Tarmizi; Saravani, Sobhan; Almisreb, Ali Abd (International Journal of Engineering and Technology, 2018)
Design of a microstrip patch UHF reader parasitic array antenna for RFID (Radio Frequency Identification) applications is proposed, in which the design patches antenna realized by loading two truncated at the corner of the ordinary rectangular patch antenna. The patch was sorted in a 2 x 2 array configuration, meanwhile the feed network was constructed by coaxial feed concept. The parasitic elements are added on the same layer of the substrate and at the right and left side of the every patch. The physical parameters of the novel structure are simulated and optimized by using commercial computer simulation technology (CST) simulation packages. The simulation results show the high gain antenna is achieved which is 11.15 dBi. The measured results of the return losses and the radiation pattern achieved a good agreement with the simulated results.
Keywords: Mirostrip patch antenna; UHF RFID reader antenna; array; parasitic elements; computer simulation technology (CST).